1992
DOI: 10.1111/j.1469-8137.1992.tb01065.x
|View full text |Cite
|
Sign up to set email alerts
|

The growth of the extramatrical mycelium of ectomycorrhizal fungi and the growth response of Pinus sylvestris L.

Abstract: SUMMARYNine ectomycorrhizal fungi bave been studied for their effect on the growth oi Pinus syhestris L. seedlings. Tbe plants were kept growing for six months in root chambers witb a changeable volume. Al! seedlings were cultivated under conditions of low substrate nutrient concentrations and they became strongly infected within a short time. We demonstrated the existence of an important negative correlation between tbe extent of the fungal development and the growth of tbe host plants. In most studies tbis r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(75 citation statements)
references
References 33 publications
6
68
1
Order By: Relevance
“…This is likely, since the former genet possessed the highest in vitro growth rates, 3-6 and 2-9 mm d~-^ on MMN and HA respectively, in a comparison of genets from different Scots pineforest stands (Sen, 1990a). Considerable differences between extramatrical mycelium growth rates of different S. bovinus genets on the same pine species has been reported by Colpaert, Van Assche & Luijtens, (1992), and in vitro growth rates of other fungal species were shown to correlate with colonization success of Scots pine root in a related microcosm study (Erland & Finlay, 1992).…”
Section: Discussionmentioning
confidence: 83%
“…This is likely, since the former genet possessed the highest in vitro growth rates, 3-6 and 2-9 mm d~-^ on MMN and HA respectively, in a comparison of genets from different Scots pineforest stands (Sen, 1990a). Considerable differences between extramatrical mycelium growth rates of different S. bovinus genets on the same pine species has been reported by Colpaert, Van Assche & Luijtens, (1992), and in vitro growth rates of other fungal species were shown to correlate with colonization success of Scots pine root in a related microcosm study (Erland & Finlay, 1992).…”
Section: Discussionmentioning
confidence: 83%
“…Wallander & Nylund (1991) found that mycorrhizal colonization reduced the sugar concentrations both in pine shoots and roots. Reductions in plant growth due to mycorrhizal formation have been recorded previously in young seedlings (Colpaert, Van Assche & Luijtens, 1992 ;Nylund & Wallander, 1989). Mycorrhizal infection did not improve N uptake into shoots.…”
Section: Effects Of Mycorrhizas On Host Plant Qualitymentioning
confidence: 79%
“…This could imply that developing mycorrhizas retained N. Higher mycorrhizal infection level together with decreased root growth in mycorrhizal seedlings at lower N level (expt 2) support this suggestion. Colpaert et al (1992) concluded that the degree of N reduction in shoots after mycorrhizal establishment was species dependent and linked with the fungal biomass. Higher mycorrhizal infection in pine roots in expt 2 at lower N availability did not increase total phenolics concentration in roots.…”
Section: Effects Of Mycorrhizas On Host Plant Qualitymentioning
confidence: 99%
“…This measure might be an appropriate index for nutrient transfer to the host plant (in AM fungi the presence of internal structures such as arbuscules implies transfer of P). However, because extraradical hyphae account for a large portion of fungal biomass (30-87% of ECM fungi ; Colpaert et al, 1992 ;, cited by Ekblad et al, 1995), direct measures of hyphal length are a valuable indicator of the mycorrhizal C pool (Rillig & Allen, 1999). Furthermore, root colonization does not necessarily increase linearly with hyphal biomass, and environmental changes might alter relationships between the two variables.…”
Section: Measures Of Mycorrhizal Response To Environmental Changesmentioning
confidence: 99%